Numerical simulation on the three-dimension mesoscopic model of aerated ceramsite concrete based on CT scan - Zhewei Liang; Chaomin Rao; Yuanchen Zhu; Timon Rabczuk; Jianmin Wang (Case Studies in Construction Materials)
As a kind of composite construction material integrated with relatively high strength and excellent acoustic and thermal insulation, aerated ceramsite concrete (ACC) characterizes with multilevel pore structures with different features in aerated cement slurry base, ceramsite aggregate and the interfacial transition zone (ITZ) respectively. It was found that pores distribution in ceramsite aggregates was relatively regular with pore walls being smooth and compact. In contrast, pore sizes and distribution in aerated cement slurry base were obviously discrete and pore walls were loose. Prominently, the ITZ was denser than both of aerated cement slurry base and ceramsite with less pores inside. To reproduce reasonable 3D mesoscopic model of ACC for effective simulation, the ACC specimen was first remodeled using MIMICS by CT scanning. The proposed simulation method well represented the real ceramsite aggregates and distribution in ACC and the result coincided with the test based on the related defining of crushable foam material model of the aerated mortar cement slurry and ceramsite aggregates. The uniaxial compressive test of ACC and simulation indicate that, the porous structure and strength matching between the aerated cement slurry base and ceramsite aggregates were the key factors to affect the mechanism and failure of ACC. The internal cracks mostly originated from the aerated cement slurry base or in the ceramsite aggregates being more porous with lower strength.